2021
DOI: 10.1002/cm.21691
|View full text |Cite
|
Sign up to set email alerts
|

Androgen downregulates desmocollin‐2 in association with induction of mesenchymal transition of breast MDA‐MB‐453 cancer cells

Abstract: Desmosomes are cellular structures that are critical in cell-cell adhesion and in maintaining tissue architecture. Changes in the expression of desmocollin-2 (DSC2) have been noted during tumor progression into an invasive phenotype and as cells undergo epithelial-mesenchymal transition. We have previously reported that breast MDA-MB-453 cancer cells, a luminal androgen receptor (AR) model of triple-negative breast cancer, acquire mesenchymal features when treated with the AR agonist, dihydrotestosterone (DHT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…This cell adhesion structure is crucial for maintaining the normal architecture of epithelial tissues. While DSC2 is involved in tumor progression and development in various types of cancer, it is known to be highly expressed in aggressive subtypes and to be correlated with poor survival outcome in patients with breast cancer [ 48 ]. Additionally, a recent experimental study of a breast cancer cell line revealed significantly greater expression of the DSC2 gene in HER2-positive patients and TNBC patients, and DSC2 overexpression was significantly correlated with shorter disease-free survival and overall survival.…”
Section: Resultsmentioning
confidence: 99%
“…This cell adhesion structure is crucial for maintaining the normal architecture of epithelial tissues. While DSC2 is involved in tumor progression and development in various types of cancer, it is known to be highly expressed in aggressive subtypes and to be correlated with poor survival outcome in patients with breast cancer [ 48 ]. Additionally, a recent experimental study of a breast cancer cell line revealed significantly greater expression of the DSC2 gene in HER2-positive patients and TNBC patients, and DSC2 overexpression was significantly correlated with shorter disease-free survival and overall survival.…”
Section: Resultsmentioning
confidence: 99%
“…Conflicting results could also be due to intrinsic molecular differences within AR based signalling within BC. Role of AR and androgens in carcinogenesis and promoting metastasis through epithelial to mesenchymal transition (EMT) is well established in prostate cancer (12).Similar trends of AR in promotion of EMT has been recently shown in in vitro models of BC (13)(14)(15). Moreover, AR is also considered a drug target in BC and AR targeted therapies have induced varied tumor responses in clinical trials (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 83%
“…The number of AR driven tumors was higher in HR+HER- and HER2+ tumors, but this trend was not observed in these subtypes. Ahram et al observed treatment with AR agonist DHT on MDA-MB-453(14) induced only partial EMT with changes in morphology from epithelial to mesenchymal phenotype but less changes in migration. Association of AR high group of tumors with better survival despite being associated with higher EMT features, perhaps is due to inability of AR in aiding invasion and migration which are crucial steps in metastases.…”
Section: Discussionmentioning
confidence: 99%
“…This cell adhesion structure is crucial for maintaining the normal architecture in epithelial tissues. While it has been studied that DSC2 is involved in tumor progression and development in various types of cancer, it is known to exhibit high expression in aggressive subtypes and to be correlated with poor survival outcome in breast cancer [39]. Additionally, a recent experimental study on breast cancer cell line revealed a signi cantly higher expression of the DSC2 gene in HER2-positive and TNBC, and DSC2 overexpression showed a signi cant correlation with a shorter disease-free and overall survival.…”
Section: Cell-cell Interactionmentioning
confidence: 99%